Perbandingan Sistem Hukum Indonesia dengan Amerika Serikat Terkait Pengaturan Jaminan Kesehatan - Savero, Ivan; Lubis, Arief Fahmi; Prasetyo, Boedi; Tetty Melina Lubis (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
A country's legal system is a fundamental aspect of health insurance. Indonesia and the United States have different approaches to regulating health insurance, both in terms of regulation, coverage of participants, and financing mechanisms. This paper compares the legal systems of Indonesia and the United States in regulating health insurance by highlighting differences in policies, legal bases, and implementation in each country. In Indonesia, health insurance is organized by the government through BPJS Kesehatan which has mandatory participation. Meanwhile, in the United States, the health insurance system is more mixed with the dominance of the private sector and public programs such as Medicare and Medicaid. This study uses a normative legal method with a comparative legal approach to analyze the effectiveness, challenges, and impacts of each system on access to and quality of health services. The results of the study show that the Indonesian system is more inclusive but faces financial sustainability constraints, while the United States system provides flexibility for participants but still experiences problems with affordability. By understanding the advantages and disadvantages of each system, this study is expected to contribute to the development of more effective and equitable health insurance policies